Storax Inhibits Caveolae-Mediated Transcytosis at Blood-Brain Barrier After Ischemic Stroke in Rats - Zhou, Min; Li, Dongna; Shen, Qian; Gao, Lei; Zhuang, Pengwei; Zhang, Yanjun; Guo, Hong (Frontiers in Pharmacology, 2022)
Background and Purpose: Blood-brain barrier (BBB) disruption following ischemic stroke (IS) contributes to hemorrhagic transformation, brain edema, increased neural dysfunction, secondary injury, and mortality. The prevailing view attributes the destruction of tight junction proteins (TJs) to the resulting BBB damage following IS. However, recent studies define a stepwise impairment of the transcellular barrier followed by the paracellular barrier which accounts for the BBB leakage in IS. The increased endothelial transcytosis that has been proven to be caveolae-mediated, preceding and independent of TJs disintegration. Emerging experimental investigations suggested Storax attenuates BBB damage after stroke. This study aimed to test our hypothesis that Storax inhibits caveolae-mediated transcytosis at BBB after ischemic stroke in rats. Methods: Male Wistar rats (250–300 g) were subjected to transient middle cerebral artery occlusion (t-MCAO). Brain water content and the cerebral infarction size were assessed by brain tissue drying-wet method and 2,3,5-triphenyltetrazolium chloride (TTC) staining. BBB permeability was detected by the leakage of Evans blue and Albumin-Alexa594. The ultrastructure of BBB was examined by transmission electron microscopy (TEM). Cav-1 and Mfsd2a were quantified by western blotting and immunofluorescence staining, AQP4, PDGFR-β, ZO-1 and Occludin were quantified by western blotting. Results: Storax treatment of 0.1 g/kg had no significant effects on brain lesions. Storax treatment of 0.2, 0.4, and 0.8 g/kg led to a significant decrease in infarction size, and the Storax 0.4, 0.8 g/kg groups displayed a significant reduction in brain water content. Storax treatment of 0.8 g/kg showed mild toxic reactions. Thus, 0.4 g/kg Storax was selected as the optimal dose for subsequent studies. Storax significantly inhibited the fluorescent albumin intensity in the brain parenchyma and the number of caveolae in ECs, alongside attenuating the ultrastructural disruption of BBB at 6 h after stroke. Meanwhile, Storax significantly increased the expression of Mfsd2a and PDGFR-β, and decrease the expression of Cav-1 and AQP4, corresponding to the significantly decreased Cav-1 positive cells and increased Mfsd2a positive cells. However, Storax has no significant effects on Evan blue leakage or the expression ZO-1, Occludin. Conclusion: Our experimental findings demonstrate Storax treatment inhibits caveolae-mediated transcytosis at BBB in the focal stroke model of rats. We also speculate that regulation of Cav-1, Mfsd2a, AQP4, and PDGFR-β expressions might be associated with its beneficial pharmacological effect, but remain to define and elucidate in future investigation.